2004
DOI: 10.1002/j.1939-4640.2004.tb02757.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Antioxidant Capacity in Pre‐ and Postoperative Varicocele

Abstract: In order to explore the impact of surgical treatment on antioxidant defense system in varicocele (VAR), we evaluated seminal total antioxidant capacity (TAC) in 25 patients affected by VAR, in 14 patients studied 10-24 months after varicocelectomy (post-VAR) and separated into normo- and oligospermic groups, and in 24 non-VAR control patients with seminal parameters matched to patients with VAR in the oligo- and normospermic groups (7 subjects with idiopathic oligospermia and 17 normal fertile subjects). TAC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…Several studies have demonstrated that the total seminal plasma antioxidant levels in patients with varicocele are decreased and DNA damage in these patients was increased [12][13][14][15][16][17][18]. Moreover, some studies have shown that varicocelectomy can improve DNA fragmentation and total antioxidant capacity [19,20]. Besides, our results in another study showed that after varicocelectomy, DFI significantly decreased compared with before surgery (Data not shown).…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have demonstrated that the total seminal plasma antioxidant levels in patients with varicocele are decreased and DNA damage in these patients was increased [12][13][14][15][16][17][18]. Moreover, some studies have shown that varicocelectomy can improve DNA fragmentation and total antioxidant capacity [19,20]. Besides, our results in another study showed that after varicocelectomy, DFI significantly decreased compared with before surgery (Data not shown).…”
Section: Discussionmentioning
confidence: 48%
“…16.1 ± 2.1 12.1 ± 3.8 a 8.7 ± 2.5 a,b 7.7 ± 2.7 a,b GPx (U ml )1 ) 5.6 ± 0.9 3.8 ± 2.2 a 2.6 ± 1.4 a,b 2.0 ± 1.7 a,b,c Vit.C (mg dl )1 ) 0. conditions being negatively correlated with sperm concentration, sperm motility and sperm normal forms percentage (Barbieri et al, 1999;Hendin et al, 1999;Mostafa et al, 2001;Mancini et al, 2004). In this study, seminal OS was investigated in infertile OAT subjects associated with their varicocele grade where there was significant increase in the investigated seminal ROS parameters and significant decrease in the studied seminal antioxidants in varicocele grades II and III cases compared with grade I cases.…”
Section: Discussionmentioning
confidence: 87%
“…Most of the articles that discussed the influence of varicocele in infertile males demonstrated increased seminal ROS in varicocele-associated conditions being negatively correlated with sperm concentration, sperm motility and sperm normal forms percentage (Hendin et al, 1999;Mostafa et al, 2001;Mancini et al, 2004). In this study, this issue was investigated as well in fertile normozoospermic males with and without varicocele.…”
Section: Discussionmentioning
confidence: 91%